2018
DOI: 10.1002/pro.3416
|View full text |Cite
|
Sign up to set email alerts
|

Functional classification of protein structures by local structure matching in graph representation

Abstract: As a result of high‐throughput protein structure initiatives, over 14,400 protein structures have been solved by Structural Genomics (SG) centers and participating research groups. While the totality of SG data represents a tremendous contribution to genomics and structural biology, reliable functional information for these proteins is generally lacking. Better functional predictions for SG proteins will add substantial value to the structural information already obtained. Our method described herein, Graph Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…A protein LBS is a key location that should be identified and characterized properly for a successful structure-based drug design campaign . In addition, locating LBS on a protein can facilitate functional annotation through their LBS structural similarity comparisons. This is particularly useful for the characterization of a large number of protein structures solved via high-throughput methods from structural genomics …”
Section: Introductionmentioning
confidence: 99%
“…A protein LBS is a key location that should be identified and characterized properly for a successful structure-based drug design campaign . In addition, locating LBS on a protein can facilitate functional annotation through their LBS structural similarity comparisons. This is particularly useful for the characterization of a large number of protein structures solved via high-throughput methods from structural genomics …”
Section: Introductionmentioning
confidence: 99%
“…The translated product was predicted to contain a signal peptide consisting of the first 18 aa located at the N‐terminus. Protein domain analysis revealed that MaLamNA contained a C‐terminal laminin‐G3 domain specified for concanavalin A‐like lectin/glucanase superfamily, suggesting a potential role of MaLamNA in biomass degradation through hydrolysis (Mills et al ., 2018). Phylogenetic analysis of MaLamNA with the characterised bacterial laminarinases of different GH families of EC 3.2.1.39 indicated that MaLamNA was not closely grouped with other members in a same family branch (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One common approach uses three-dimensional (3D) convolutional neural networks. Concentric shells surrounding specific protein sites can also be used to represent the spatial distribution of biochemical properties . Other methods use graph representations of enzymes and their active sites. , For example, Gligorijević et al generate amino contact maps from protein structures and use the resulting adjacency matrix as input for a graph convolutional network. The distribution of torsion angles and pairwise distances, extracted for each amino acid (AA) type separately, can also generate feature maps for downstream protein or enzyme functional prediction. , …”
Section: Introductionmentioning
confidence: 99%